Coding‐Feeding Metasurface for Diffusion and Dual‐Band Emission (Adv. Theory Simul. 8/2022). Issue 8 (11th August 2022) - Huang, Guo Shuai; Li, Si Jia; Li, Zhuo Yue; Liu, Xiao Bin; Ji Di, Liao Ri; Cao, Xiang Yu
Abstract : Coding‐Feeding Metasurface for Diffusion and Dual‐Band Emission In article 2200006, Si Jia Li and co‐workers develop a new type of coding‐feeding metasurface by combining an emission patch and two arc triangle patches for polarization conversion in a shared aperture, digitally realizing the scattering diffusion and dual‐band radiation simultaneously. This metasurface with a lightweight, compact and low profile has potential applications in stealth aircraft systems and wireless communications.